Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Home Industry Tahu Bulat Jempol Ciamis (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to determine the simultaneous and partial influence of Work Discipline and Work Environment on the Performance of Employees of the Ciamis Tahu Bulat Jempol Home Industry Company. The research method used is a quantitative method with a survey approach. The sampling technique used saturated samples with a sample size of 50 people. The data collection technique uses an offline questionnaire. The data used is primary blood. The analytical tool used in this research is Multiple Linear Regression using SPSS 25. The research results show that simultaneously Work Discipline and Work Environment have a significant effect on Employee Performance. Partially, work discipline has a significant effect on employee performance. Partially, the work environment has a significant effect on employee performance.